On-Field Ski Kinematic According to Leg and Discipline in Elite Alpine Skiers - Alhammoud, Marine; Hansen, Clint; Meyer, Frederic; Hautier, Christophe; Morel, Baptiste (Frontiers in Sports and Active Living, 2020)
This study used wireless technology to investigate joint kinematic characteristics of the four alpine skiing disciplines. Knee and hip angles were measured in 20 national team alpine skiers during 253 ski runs under FIS regulation, including: 85 Slalom (SL), 123 Giant Slalom (GS), 29 Super Giant Slalom (SG), and 16 Downhill (DH). Data were analyzed by outside (OL, n = 2,087) and inside leg (IL, n = 2,015). The proportion of concentric and eccentric phases (extension and flexion respectively for the knee extensors) as well as the proportion of the quasi-isometric phase defined between ±20°.s−1 depended on the discipline in interaction with the IL/OL (p < 0.001). The results showed a lower knee quasi-isometric duration on OL in SL (11%) than other disciplines (DH: 38%; SG: 42%; GS: 34%, p < 0.001, d > 1.8), suggesting a highly dynamic style. Quasi-isometric mode was significantly longer on OL than IL in GS (34 vs. 20%, p < 0.001, d = 1.16) and SG (42 vs. 28%, p < 0.001, d = 1.11) but was significantly longer on IL than OL in SL (19 vs. 11%, p < 0.001, d = 0.64). Thus, GS and SG showed similarities, with a significantly faster knee eccentric mean angular velocity on IL compared to OL (GS −58 vs. −54°.s−1, SG −52 vs. −45°.s−1, p < 0.001, d ≥ 0.22) whereas SL showed an opposite pattern (−72 vs. −89°.s−1, p < 0.001, d = 1.10). The quasi-isometric phase was overlooked in previous studies but is crucial to consider. The current data may be used to train the outside and inside leg specificities incorporating discipline-specific contraction modes and exercises.